Effects of education level and employment status on HRQoL in early relapsing-remitting multiple sclerosis - Patti, F.; Pozzilli, C.; Montanari, E.; Pappalardo, A.; Piazza, L.; Levi, A.; Onesti, E.; Pesci, I. (Multiple sclerosis, 2007)
Purpose To evaluate the effects of education level and employment status on health-related quality of life (HRQoL) in a large cohort of patients affected by relapsing-remitting multiple sclerosis (RRMS). Patients This study included 648 patients with RRMS attending 40 Italian MS centers. Inclusion criteria were an Expanded Disability Status Scale (EDSS) score between 1.0 and 5.5; stable disease on enrollment; and no previous treatment with interferons, glatiramer acetate, or immunosuppressive drugs. Quality of life (QoL) was evaluated by the Multiple Sclerosis Quality of Life-54 questionnaire (MSQoL-54). Results Employed patients scored significantly higher than other patient groups in the majority of MSQoL-54 domains. Similarly, patients with academic degrees and secondary education had higher scores than those with primary education (ie, eight years of education) in several domains of HRQoL. Patients who were employed with a high educational level achieved significantly better scores than unemployed patients with a lower educational level. In multivariate analysis, occupation and educational level were found to be significant and independent predictors of HRQoL. Conclusions The results of our study suggest the importance of sustaining employment after a recent diagnosis of MS. In addition, education has a great influence on HRQoL; a higher education level may determine a stronger awareness of the disease, and a better ability to cope with the challenges of a chronic disease such as MS. Multiple Sclerosis 2007; 13: 783-791. http://msj.sagepub.com